Effectiveness of extract and fraction of robusta coffee beans (coffea canephora) against streptozotosin-nicotinamide induced blood glucose levels of male white mice - Risny Oklyan; Tri Wijayanti; Gunawan Pamudji Widodo (Journal of Health Management and Pharmacy Exploration, 2026)
Robusta coffee bean have compounds flavonoids, alkaloids, saponins and tannins. This compound has the benefit of being an antihyperglycemic which plays a role in inhibiting absorption glucose, preventing the formation of AGEs chains, and increasing the activity of antioxidant enzymes. This research aims to determine the effectiveness of the robusta coffee bean fraction which is effective in reducing blood glucose levels in STZ-NA induced mice. Research conducted is experimental research. Using 30 mice aged 2-3 months with a body weight of 18-25 g and grouped into 6 groups, that is group I negative streptozotocin 5.6 mg/kg weight and nicotinamide 15.4 mg/kg weight, group II positive control was given glibenclamide 0.65 mg/kg weight, Group III was given robusta coffee bean extract 400 mg/kg weight Group IV was given the n-hexane fraction of 42 mg/kg weight, group V was given the ethyl acetate fraction of 38 mg/kg weight, group VI was given the water fraction of 216 mg/kg weight. The data has been analyzed and after 21 days of observation it was found that the ethyl acetate fraction and robusta coffee bean extract decreased blood glucose levels the same as the decrease in blood glucose levels in the positive group test.